Destination Branding Di Geopark Silokek Untuk Mendukung Promosi Wisata - Hendra; Aryonoi Ananta; Rifaldi (Besaung : Jurnal Seni Desain dan Budaya, 2026)
Silokek Geopark in Sijunjung Regency is a region with geological, biological, and cultural richness that has the potential to become a world-class tourist destination. However, this area lacks a strong visual identity and a structured digital promotion strategy to strengthen its image as a leading destination. This study aims to design a destination branding system that reflects the local character of Silokek Geopark and supports image strengthening through digital branding. The method used is descriptive qualitative research with a Design-Based Research (DBR) approach. Data collection was carried out through observation, in-depth interviews with local stakeholders, documentation studies, and Focus Group Discussions (FGDs). The results of the study are a design for the destination's visual identity, its implementation guidelines (brand guidelines), and a digital branding strategy relevant to the characteristics of the target audience. The resulting design is the result of a visual study of Silokek's characteristics implemented in the form of a logo that represents the local wisdom of the area. The logo can be applied to various promotional media such as souvenirs, social media branding, and billboards at tourist sites. This design not only produces visual artwork but also serves as an instrument for strengthening regional identity and empowering local communities in sustainable, culture-based tourism management. The research output is a scientific publication aimed at publicizing the tourism potential and advantages of the Silokek Geopark through visual branding.